The key role of depression and supramarginal gyrus in frailty: a cross-sectional study - Isernia, Sara; Blasi, Valeria; Baglio, Gisella; Cabinio, Monia; Cecconi, Pietro; Rossetto, Federica; Cazzoli, Marta; Blasi, Francesco; Bruckmann, Chiara; Giunco, Fabrizio; Sorbi, Sandro; Clerici, Mario; et al. (Frontiers in Aging Neuroscience, 2023)
Background The age-related decrease in reserve and resistance to stressors is recognized as frailty, one of the most significant challenges identified in recent years. Despite a well-acknowledged association of frailty with cognitive impairment, depression, and gray matter morphology, no clear data are available regarding the nature of this relationship. This cross-sectional study aims to disentangle the role of the behavioral, neuropsychological, and neural components as predictors or moderators of frailty. Methods Ninety-six older adults (mean age = 75.49 ± 6.62) were consecutively enrolled and underwent a clinical and MRI (3 T) evaluation to assess frailty, physical activity, global cognitive level, depression, wellbeing, autonomy in daily living, cortical thickness, and subcortical volumes. Results Results showed a full mediation of depression on the link between cortical thickness and frailty, while the cognitive level showed no significant mediating role. In particular, left supramarginal thickness had a predicting role on depression, that in turn impacted frailty occurrence. Finally, handgrip weakness was an early key indicator of frailty in this study’s cohort. Conclusion These data substantiate the role of depression in mediating the link between neural integrity of the supramarginal gyrus and frailty. In the complexity of frailty, handgrip weakness seems to be an early key indicator. These results are relevant for the design of rehabilitation interventions aimed at reversing the frail condition.